Noun Phrase Construction Found in Recount Genres on the First Year Senior High School Students’ Textbooks: Kontruksi Frasa Kata Benda Genre Recount di Buku Tulis Sekolah Menengah Atas Kelas 10 - Dina Mauliddia; Fika Megawati (Academia Open, 2021)
This thesis analyzes types of noun phrase construction in Senior high school students’ textbooks found in recount genre. The source of data in this research are chosen report text in three different textbooks, such as “Bahasa Inggris SMA/MA/SMK/MAK kelas X, Pathway to English untuk SMA/MA Kelas X, Forward an English Course for Vocational High School Students Grade X. Result of this research is noun phrase structured from pre-modifier, head, and post- modifier. The majority pattern of noun phrase that found in text was consist of (Det+head), (Det+head+PP+CL), (Det+head+PP), and (Det+head+CL) with most of determiner was “a” and “the” as the pre-modifier. Researcher hopes that this research helps teachers in teaching and learning process, and students will able to improve their writing skills with better understanding about noun phrase construction and using it in their written product.